Análise das correlaçõs entre as musculaturas periféricas e respiratórias com a capacidade funcional de idosos comunitários - Leonardo de Assis Simoes (2007)
Introduction: In older people, the reduced capacity of skeletal muscles to produce strength is related to loss of muscle mass, named sarcopenia. This could be present either in peripheral or respiratory muscles and it would impair functional capacity. The objectives of the present study were measure the strength of peripheral muscles (knee flexors and extensors) and respiratory muscles, as well as to explore the possible correlations between these muscles and the functional capacity in the elderly. Material and Methods: Sixty five elderly 71,7(4,9) years old participated. They were divided into two groups: 65 to 75 and 76 to 85 years old. The average peak torque (APT) and average power (AP) from knee flexor and extensor muscles were measured with the isokinetic dynamometer Biodex System 3 Pro® at 60º/s, 120º/s e 180º/s; maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) from respiratory muscles were measured with the analogic manovacuometer Gerar® Classe B; and the Six Minute Walk Test (6MWT) was used as an outcome of the elderly functional capacity. The Mann-Whitney and the t-Student tests were used for comparisons between the groups. The correlations between respiratory muscles, knee flexor and extensor muscles and the 6MWT were explored using the Pearson correlation coefficient. The level of significance was set at =0.05 for all tests. Results: There was observed that peripheral and respiratory muscle strength and walking distance variables were higher in men when compared to women (p<0.05). However, when comparing between groups ages there were no significant differences for those variables, although lower mean values were found for the group of the oldest elderly. Moderated and significant correlations between APT and MIP (r=0,587), APT and MEP (r=0,638), knee extensor AP (r=0,614) and flexor AP (r=0,539) with the walking distance, MIP (r=0,508) and MEP (r=0,541) with the walking distance, respectively were found. Conclusions: These results showed a relationship between higher muscle strength and higher walking distance. This suggests that it is necessary to optimize muscle function in prevention and rehabilitation programs to maintain and to improve the functional capacity in dwelling-elderly.